An excel-based Sudoku puzzle generator and solver - Muhamad Norfaizal Mohamed Paudi (2019)
Sudoku is a popular Japanese puzzle game that requires participants to fill up a 9×9 grid with numbers so that each row, column and 3×3 section contain all the digits between 1 and 9. It is a game that tests on one's logical reasoning and can be beneficial since it improves on concentration and overall mental capacity. The main objective of this project is to explore how Microsoft Excel VBA can be used as a platform for generating and solving Sudoku puzzles. We will explore more on variety of grid configuration. We will focus on approach to generate arbitrary size Sudoku. For example, 3x3, 4x4 and 9x9 grid. For this project, Microsoft Excel VBA will be used as it is readily available with many efficient function commands, making the process easier for the project. In the later part of this report, we will discuss more on the motivation of this project from an educational point of view. The potential benefits and usefulness in developing children’s number skill will be discussed.